1993
DOI: 10.1093/clinchem/39.3.448
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of deoxyribonuclease I activity in human tissues and body fluids by a single radial enzyme-diffusion method

Abstract: In the single radial enzyme-diffusion (SRED) method for assay of deoxyribonuclease I, a precisely measured volume of the enzyme solution is dispensed into a circular well in an agarose gel layer in which DNA and ethidium bromide are uniformly distributed. A circular dark zone is formed as the enzyme diffuses from the well radially into the gel and digests substrate DNA. The diameter of the dark circle of hydrolyzed DNA increases in size with time and correlates linearly with the amount of enzyme applied to the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
124
0
5

Year Published

1997
1997
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 215 publications
(130 citation statements)
references
References 1 publication
1
124
0
5
Order By: Relevance
“…The test is similar in principle to the radial immunodiffusion method for measuring antigen concentration in agarose gels using a specific antibody [27]. A comparable method, but with different solutions and conditions, was used for measuring serum DNase I by Chitrabamrung et al [8] and Nadano et al [9]. Conditions to maximize detection of DNase-low salt concentration and a high ratio of DNA/DNasewere used.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The test is similar in principle to the radial immunodiffusion method for measuring antigen concentration in agarose gels using a specific antibody [27]. A comparable method, but with different solutions and conditions, was used for measuring serum DNase I by Chitrabamrung et al [8] and Nadano et al [9]. Conditions to maximize detection of DNase-low salt concentration and a high ratio of DNA/DNasewere used.…”
Section: Discussionmentioning
confidence: 99%
“…DNase activity in murine serum has also been assayed by a synthetic end-labelled oligonucleotide substrate assay (D. Sinicropi, personal communication). Chitrabamrung et al [8] and Nadano et al [9] have reported the measurement of DNase I activity in human tissues and body fluids by single radial enzymediffusion methods. The method is based on the hydrolysis of DNA in a DNA-agar plate.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…It is interesting to note that although there are three different isoforms of the enzyme, produced by six known polymorphisms, there are no significant differences in enzyme activity between these isoforms [26]. To fully elucidate the genetic contribution of DNASEI to the aetiology of SLE, identification of further SNPs across each isoform of the enzyme will be necessary, prior to detailed association studies in different racial groups.…”
Section: Dnaseimentioning
confidence: 99%